INVENTARISASI POHON UNTUK PENGELOLAAN POHON ASUH DI HUTAN ADAT RANTAU KERMAS DESA RANTAU KERMAS KECAMATAN JANGKAT KABUPATEN MERANGIN PROVINSI JAMBI - Ahmad Salim Ridwan; Paus Iskarni; endah Purwaningsih (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
ABSTRACT This study aimed to determine the types, location and that management in Indigenous Forests Rantau Kermas. The method used in this study was a blend of quantitative and qualitative research methods. Quantitative research methods used are collecting data about the inventory of trees that can be used as a Tree Adoption and that location. Whereas qualitative research methods, explained and described the indigenous forest management and Tree Adoption in Indigenous Forest of Rantau Kermas. The determination of research informant was done by using Purposive Sampling. The data were collected through the documentation study, field surveys and interviews. The data analysis technique used was Overlay, Buffer, and Clip. The results of the study revealed that there were 743 trees could be used as Tree Adoptions and there were 124 as Tree Adoption. Based on researcher there were 372 eligible for Tree Adoptions candidate and 104 Tree Adoptions. Indigenous Forest Management and Tree Adoption in Indigenous Forest of Rantau Kermas still used the traditional system was included rules of Indigenous Forests Kara Jayo Tuo. The criteria taken in the management of Tree Adoptions are: a) the tree caregivers were the donors who concerned with environmental issues. b) the tree managers were the villagers of Rantau Kermas commanded by a Indigenous Forest Management Group. Indigenous forest management and Tree Adoption had ecological benefits, economic sides, and socials sides.